Relationship Between Motive, Credit Card, Information, Peer and Frequency with Compulsive Buying Tendency - Mohamad, Ali (2004)
Compulsive buying is a chronic, repetitive buying that becomes a primary respond to negative feelings. It is also known as addictive behavior. People who are involved in this negative behavior have the tendency to face financial and social problems such as divorce, debt, and personal bankruptcy. Compulsive buyers are also known for having low self-esteem, materialistic, a high level of tendency to fantasize, depression, anxiety, obsession and feeling of guilt after purchase. In this study, the variables been used are hedonic motivation, credit cards use, unplanned purchase, peer influence. TV viewing and shopping frequency. The study also to identify the cross gender in compulsive buying tendency. The results exhibited the positive correlation of hedonic motivation, credit card use and unplanned purchases with compulsive buying tendency. There are three theoretical implications have been created from the finding and they are Hedonic Motive. Perceive Buying Capacity and Direct Marketing Stimuli. This study has discovered the opportunities for further study regarding compulsive buying tendency in Malaysia.